Two Cases of Ambigious Genitalia - Samina Tariq; iqbal A Memon; Ainey Razzak; Asma Aijaz (Journal of the Dow University of Health Sciences, 2010)
The term â€œAmbiguous genitaliaâ€ applies to confusing appearance of the external genitalia. Sex assignment becomesessential for the parentâ€™s peace of mind, and in turn depends on anatomy and functional endocrinology rather than karyotype. 1Two cases with all different genetic sex, gonadal sex and phenotypic sex are described. First case is that of congenital adrenal hyperplasia (CAH) in a month old baby whose genotype was female withlaboratory investigations exposing her diagnosis. She is doing well with oral hydrocortisone and fludrocortisone. Secondcase is th a t o f pro b ab le 5-alpha red u c tase d eficien cy who would pro b ab ly need future surgery.